Resolving Inflammation: Synthesis, Configurational Assignment, and Biological Evaluations of RvD1n−3 DPA. Issue 6 (20th December 2018) - Tungen, Jørn Eivind; Gerstmann, Lisa; Vik, Anders; De Matteis, Roberta; Colas, Romain Alexandre; Dalli, Jesmond; Chiang, Nan; Serhan, Charles Nicholas; Kalesse, Markus; Hansen, Trond Vidar
Abstract: New drugs that can resolve inflammation without immunosuppressive effects are at the medicinal chemistry frontier. Pro‐resolving endogenously formed small molecules, that is, the resolvins, are excellent candidates displaying such bioactions. The first total synthesis of the specialized pro‐resolving mediator RvD1 n −3 DPA has been achieved using the underutilized sp 3 –sp 3 Negishi cross coupling reaction and an alkyne hydrosilylation–protodesilylation protocol. Biological evaluations revealed that this novel mediator displays low nanomolar pro‐resolving properties and potently activates the human DRV1/GPR32 receptor. As such, this endogenous natural product is a lead compound for the development of novel immunoresolvents. Abstract : Two synthetic methods seldom used in total synthesis of natural products paved the way for the first total synthesis of RvD1 n −3 DPA . The concise preparation of multi‐mg quantities of this chemically sensitive lipid mediator allowed extensive in vivo and in vitro biological studies.